2022
DOI: 10.18041/1900-0642/criteriolibre.2021v19n35.8371
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation: importance, evolution, and emerging approaches using scientometric analysis

Abstract: The purpose of this review is to explore the importance, evolution, and emerging approaches to market orientation. The method had three steps: irstly, the importance of the topic was analyzed through the main scientometric metrics such as the number of publications per year; secondly, tree of science algorithm was applied to understand evolution. And thirdly, a citation analysis was performed to generate the approaches. The results show three approaches: product innovation, organization performance, and intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…In this topic, structural works are grouped that link the theoretical foundation of the classics with current research; and finally, the leaves (high outdegree), where most of the recent studies are found and others are cited (Wallis, 2007); these publications show the current framework guidelines for research in the area that are established as emerging research fronts. This methodological process has been used and validated in previous studies (Clavijo-Tapia et al, 2021;Ramos et al, 2021;Torres et al, 2021;Trejos-Salazar et al, 2021;Duque et al, 2021a,b;Rubaceti et al, 2022).…”
Section: Second Phase: Network Analysismentioning
confidence: 99%
“…In this topic, structural works are grouped that link the theoretical foundation of the classics with current research; and finally, the leaves (high outdegree), where most of the recent studies are found and others are cited (Wallis, 2007); these publications show the current framework guidelines for research in the area that are established as emerging research fronts. This methodological process has been used and validated in previous studies (Clavijo-Tapia et al, 2021;Ramos et al, 2021;Torres et al, 2021;Trejos-Salazar et al, 2021;Duque et al, 2021a,b;Rubaceti et al, 2022).…”
Section: Second Phase: Network Analysismentioning
confidence: 99%
“…We applied the new implementation of the ToS algorithm (SAP) that simulates the sap process of the three (see more [17] for a deeper understanding). The ToS algorithm has been used in a wide variety of research topics such as marketing [18], entrepreneurship [19,20], education [21], psychology [22], and economics [23]. Moreover, within a year of launch, ToS had around 5000 users [24].…”
Section: Tree Of Science (Tos)mentioning
confidence: 99%
“…En seguida, se efectúa una minería de texto en el programa R mediante el paquete WordCloud (Ohri, 2012); se toma de cada clúster las palabras clave y los títulos de cada trabajo, para después generar las nubes de palabras que permiten identificar de forma más fácil los temas que componen cada clúster. Este diseño metodológico ha sido empleado por otros estudios (Castellanos et al, 2022;Clavijo-Tapia et al, 2021;Díez et al, 2022;Duque, Meza, et al, 2021;Giraldo et al, 2022;Torres et al, 2021).…”
Section: Selección De Datosunclassified